From Bean to Benefit: How Indonesian Intellectual Property (IP) Law Protects the Coffee Farmers in Indonesia? - Waspiah, Waspiah; Niravita, Aprila; Naelufar, Rizqan; Putri, Nadiyah Meyliana; Eka Saputra, Dany (Jambe Law Journal, 2024)
This study addresses the urgent question: How can legal protections for Geographical Indications (GIs) as a form of Intellectual Property (IP) enhance the welfare of coffee farmers in Temanggung, Indonesia? Coffee is a vital agricultural product in this region, yet farmers face challenges in maximizing its economic potential. The research positions itself within the framework of empirical legal studies, analyzing the interplay between legal protections and agricultural sustainability. The paper discusses the issue by first examining the current state of GI protection in Temanggung, identifying both obstacles faced by farmers and the government. Through qualitative analysis, the study evaluates effective strategies for implementing GI protections and their implications for farmer welfare. The main findings indicate that while there are significant challenges in enforcing GI protections, targeted strategies—such as regular training and outreach for farmers, improved marketing initiatives, and the establishment of local regulations—can substantially enhance their livelihoods. Moreover, the research highlights the importance of increasing awareness and knowledge among farmers to leverage GI protections effectively. Overall, this study contributes to the understanding of agricultural law's role in rural development, providing actionable insights for policymakers and stakeholders aiming to support Indonesia’s coffee farmers.